Comment on "3D squeezed flow of γAl2O3–H2O and γAl2O3–C2H6O2 nanofluids: A numerical study, Int. J. Hydrogen Energy 42 (2017) 24620–24633". (15th November 2018) - Nademi Rostami, Mohammadreza; Dinarvand, Saeed
Abstract: The present comment concerns the improvement of the similarity energy equation that has been written incorrectly in the article by Khan et al. [1]. In this note, we derive its correct form and show that such a mistake may affect the results.